1993
DOI: 10.1103/physrevb.48.13904
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling measurements of the electron-phonon interaction inBa1xK

Abstract: The conductance curves of point-contact tunnel junctions between Ag and Ba1−xKxBiO3 (x 0.4) reveal a BCS behavior with low leakage current at zero voltage and some broadening of the superconducting-gap structure. In the energy range above the superconducting energy gap, the structure in the voltage dependence of the second derivative d 2 V /dI 2 of the voltage with respect to the current of the tunnel junction has been investigated in detail in magnetic fields up to 10 T . While part of this structure is rapid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…In our case with l/ξ 0 about ∼ 0.7 also the strong-coupling plays an important role as shown in ref. [30].…”
Section: Resultsmentioning
confidence: 99%
“…In our case with l/ξ 0 about ∼ 0.7 also the strong-coupling plays an important role as shown in ref. [30].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas isotope effects are generally no direct measure of phonon involvement in superconductivity (see e.g. [19] ), the uniqueness of a (supposedly close) correspondence between the Eliashberg spectral function ~2F(to) and the phonon density-ofstates is experimentally difficult to demonstrate [25,26]. Ab initio calculations show little sign of such a relation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Upon comparing the functions F(to) and ~2F(~o) it is found that their frequency dependence is entirely different, which is surprising in view of the tunneling results [25,26]. With decreasing (K,Pb) doping, ~2F(og) shifts markedly to lower frequencies and develops more intensity, especially in the range 20-40 meV, whereas the phonon density-of-states F(og) is much less sensitive.…”
Section: Direct Calculations Of Parametersmentioning
confidence: 93%
See 1 more Smart Citation
“…The only spurious feature is a dip outside the gap at ±5 mV. Such dips could originate from a redistribution of the current path when a critical current is reached in a weak link or a crack nearby the contact [15]. This efect is hardly avoidable in the powder samples.…”
mentioning
confidence: 99%